P136 Multidimensional prognostic index for exacerbations of COPD. (14th November 2013) - Short, PM; Williamson, PA; Singanayagam, A; Akram, A; Schembri, S; Chalmers, JD
Abstract : Introduction and Objectives: Prognostic assessment of COPD exacerbations is currently limited by models that only take into account short term prognostic factors. We developed a multidimensional tool for COPD exacerbations, predicting both short and long term outcome. Methods: A prospective multicentre, UK observational cohort of patients hospitalised with exacerbations of COPD 2009–2011. Cox-proportional hazards regression used to identify independent predictors of 30-day and 1 year mortality. Two independent risk scores based on exacerbation severity (acute score) and severity of COPD and co-morbidities (chronic score) were developed. The two scores were then used to generate a 4 class decision grid based on the GOLD 2011 criteria for stable COPD. Results: 1343 patients were included. 749 patients were readmitted or died during 1 year follow-up. Predictors of 30-day mortality (acute score) were new onset confusion HR 2.23 (95%CI 1.34–3.71)- 1 point, Urea >7mmol/L 2.64 (95%CI 1.51–4.61)- 1 point, acidosis 4.22 (95%CI 2.68–6.65)- 2 points, glucose >8mmol/L 1.56 95%CI (1.00–2.46)- 1 point and albumin <35g/L 2.23 (95%CI 1.42–3.5)- 1 point and heart rate >110bpm 2.37 (95%CI 1.50–3.73)- 1 point. The AUC for 30 day mortality for the acute score was 0.84 (95%CI 0.80–0.88). The strongest predictors of 1 year mortality were age >80 years HR 1.25 (95%CI 1.00–1.64)–1 point, neoplastic disease 1.91 (95%CI 1.37–2.65)–1 point, MRC dyspnoea grade 4 or 5 (3.82 95%CI 2.61–5.58)- 2 points, FEV1 <30% predicted 2.61 (95%CI 1.99–3.43)–1 point, long term oxygen therapy 1.60 95%CI 1.11–2.29)–1 point and a history of myocardial infarction or heart failure 2.76 95%CI 1.70–4.47)–1 point. The AUC for 1 year mortality of the chronic score was 0.76 (95%CI 0.73–0.80). The resulting 4 stage model identifies different outcomes within each subgroup (See Figure 1 ). Furthermore the 4 stage model predicted 30-day mortality AUC 0.76 (95%CI 0.72–0.79), 1 year mortality 0.72 (95%CI 0.70–0.74) and readmissions 0.74 (95%CI 0.72–0.76) better than GOLD 2011 criteria. Conclusion: A multidimensional prognostic index can predict both short and long term outcomes after COPD exacerbations, and divides patients into clinically useful subgroups based on exacerbation severity and chronic health status.